2015
DOI: 10.1037/a0037676
|View full text |Cite
|
Sign up to set email alerts
|

Modeling criterion shifts and target checking in prospective memory monitoring.

Abstract: Event-based prospective memory (PM) involves remembering to perform intended actions after a delay. An important theoretical issue is whether and how people monitor the environment to execute an intended action when a target event occurs. Performing a PM task often increases the latencies in ongoing tasks. However, little is known about the reasons for this cost effect. This study uses diffusion model analysis to decompose monitoring processes in the PM paradigm. Across 4 experiments, performing a PM task incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
102
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(123 citation statements)
references
References 75 publications
(202 reference statements)
16
102
4
Order By: Relevance
“…Horn and Bayen (2015) similarly found that PM demands produced changes in threshold, but not drift rate, but additionally found that variables thought to influence the degree of monitoring enacted (i.e., importance of intention, cue frequency, and cue focality) selectively increased nondecision time. Together these results suggest that PM costs may reflect both response caution and target-checking, as indicated by changes in boundary separation and nondecision time, respectively, rather than decreased processing efficiency (i.e., drift rates).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Horn and Bayen (2015) similarly found that PM demands produced changes in threshold, but not drift rate, but additionally found that variables thought to influence the degree of monitoring enacted (i.e., importance of intention, cue frequency, and cue focality) selectively increased nondecision time. Together these results suggest that PM costs may reflect both response caution and target-checking, as indicated by changes in boundary separation and nondecision time, respectively, rather than decreased processing efficiency (i.e., drift rates).…”
Section: Introductionmentioning
confidence: 77%
“…Participants performed an ongoing lexical decision task with a nonfocal intention (monitor for the “tor” syllable) and were either instructed that it was more important to detect all the PM cues (PMI condition), or that it was more important to do well on the ongoing task (ongoing task importance, or OTI, condition). Prior research with young adults has demonstrated that PMI instructions generally increase cue detection at the cost of ongoing task performance (Horn & Bayen, 2015; Loft et al, 2008). However, the influence of importance on PM in the context of aging is mixed, with one study showing a selective benefit in cue detection from PMI instructions for older adults (Hering et al, 2013), one showing a benefit for both age groups (Smith & Hunt, 2014), and one showing no effect for either age group (Kliegel, Martin & Moor et al, 2003).…”
Section: Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, by investigating parameters from the ex-Gaussian distribution in younger adults, Loft et al [32] revealed a shift in the entire response time distribution (μ) in a nonfocal compared to a focal PM condition (indicating a more continuous PM monitoring profile in nonfocal PM) and an increase in skew (τ) in the nonfocal compared to the focal condition (indicating lapses of attention in nonfocal PM). Horn and Bayen [33] showed with the diffusion model approach that increases in peripheral nondecision time emerged in a nonfocal (but not in a focal) PM task, possibly reflecting a PM-target-checking strategy before and after the ongoing decisions. In addition, comparing IIV in younger and older adults, Horn et al [34] found that such increases in peripheral nondecision time in a nonfocal PM task were larger for older than for younger adults, possibly indicating older adults' lower capacity to recruit additional executive resources for PM-target checking).…”
Section: Major Issues For the Next Decadementioning
confidence: 99%